A Comparative Evaluation and Pharmacological Assessment of Abelmoschus Manihot Leaves Extract in Vitro Antidiabetic, Neuroprotective Activities, and their Effects on Glucose Uptake and DPP-4 Inhibition - Ramenani Hari Babu; Maneesha Bhardwaj; B.R Asokan; Deblina Sardar; P.V.R Teja Sruthi; Aniruddha Mukherjee; Dinesh Vishwakarma; Vema Kiran (The Bioscan, 2024)
The present research was designed to pharmacologically evaluate the leaves of Abelmoschus manihot using various mechanistic models. The plant leaves were extracted using the Soxhlet extraction method, and the resulting extracts underwent preliminary phytochemical screening. The methanol extract (AMLE-M) was further assessed for its pharmacological activity in antidiabetic, antioxidant, and neuroprotective models. Phytochemical analysis confirmed the presence of phenols, flavonoids, alkaloids, and proteins in AMLE-M. The total phenolic content of the extract was 319.69 mg GAE/g. In mechanistic antidiabetic models, AMLE-M enhanced glucose utilization in L6 myoblasts in a dose-dependent manner, with a significant increase observed at 25 μg/mL. Inhibition of DPP-4, a key enzyme in diabetes management, was also observed, with a maximum inhibition of 42.79% at 125 μg/mL. In antioxidant models, AMLE-M significantly reduced intracellular reactive oxygen species (ROS) levels under H₂O₂-induced oxidative stress, with ROS levels decreasing to 166% at 48 μg/mL from 289% in the control. These findings suggest that AMLE-M possesses notable antioxidant, antidiabetic, and neuroprotective activities, highlighting its potential for therapeutic applications in oxidative stress and glucose-related disorders.